Propionimicrobium gen. nov., a new genus to accommodate Propionibacterium lymphophilum (Torrey 1916) Johnson and Cummins 1972, 1057AL as Propionimicrobium lymphophilum comb. nov. - Stackebrandt, Erko; Schumann, Peter; Schaal, Klaus P; Weiss, Norbert (International Journal of Systematic and Evolutionary Microbiology, 2002)
Based upon significant differences in chemotaxonomic properties, i.e., amino acid composition of peptidoglycan, fatty acids and base composition of DNA, and supported by the phylogenetic position of the 165 rDNA sequence the species Propionibacterium lymphophilum was reclassified as Propionimicrobium lymphophilum comb. nov.